Educação em economia popular solidária: o discurso educativo de incubadoras de empreendimentos solidários populares - Santana, Clécia Rufino de (2012)
This thesis aims to analyze university extension projects, directed to solidarity popular economy. This way of doing economics has been expressed as an international movement, and that here, in Brazil, is mostly perceived in public universities since the mid-90s of last century, from the Technological Incubators of Popular Cooperatives (ITCPs), which are a university extension program and that encourage solidarity and popular projects, seeking to exercise self-management. The research sought to answer the following question: what educational components are present in the extension developed by incubators of solidarity popular enterprises? The basic hypothesis is that the university extension developed by popular incubators presents ethical, theoretical and methodological components which converge with basic elements to popular education. The research was qualitative in nature, based on the theory of historical materialism, assuming the materialist dialectics as a method of analysis, prioritizing the contradiction category. Based on Marxist analysis, however, this research emphasized the interpretation, setting up what is called a dialectical hermeneutics. It took part of the empirical field of the research four incubators, namely INCUBACOOP/ UFRPE, ITCP/COPPE/UFRJ, ITCP/USP and INCUBES/UFPB. It was used as a technique for data collection, documents produced by the incubators and semistructured interviews, strengthening the documentary analysis. The data showed that the incubators of solidarity popular projects present themselves as a new and rich proposal of extension, able to build concrete possibilities of a transformative praxis, based on the ethical principles of dialogue, appreciation of the cultures of others, participation and listening, this is, consideration of the speaking of others; and yet, based in the utopian principles of autonomy, self-management and human emancipation, present in popular education. Paradoxically, the implementation of these educational acts revealed professionals that although were already working in the solidarity economy, ignored the theoretical-methodological bases of the educational proposal of incubator, it also revealed a verticalized internal structure and consequent centralization of the power of decisions within it, besides the methodological sight of incubation simply summarized to techniques.